Impact of human papillomavirus infection on semen parameters and reproductive outcomes - Hana Jaworek; Vladimira Koudelakova; Ivana Oborna; Blazena Zborilova; Jana Brezinova; Dagmar Ruzickova; Jana Vrbkova; Pavla Kourilova; Marian Hajduch (Reproductive Biology and Endocrinology, 2021)
Abstract Background Human papillomavirus (HPV) has been shown to adversely affect human reproduction. We aimed to evaluate the prevalence of human papillomavirus (HPV) infection in men and its correlation with semen parameters and reproductive outcomes. Methods Semen samples and penile swabs were collected from potential sperm donors (SD, n = 97) and male partners of infertile couples (IM, n = 328). The presence of HPV DNA in semen samples and penile swabs was analyzed. Associations between hrHPV positive status and fertility outcomes as well as socio-behavioral and health characteristics were evaluated using the R software package. Results High-risk HPV (hrHPV) genotypes were detected in 28.9% of SD and 35.1% of IM (P = 0.312). Penile swabs were more frequently positive for hrHPV genotypes than semen samples in both IM (32.3% vs. 11.9%, P < 0.001) and SD (26.8% vs. 6.2%, P = 0.006). Men with hrHPV positive semen samples had lower semen volume (median volume 2.5 ml vs. 3 ml, P = 0.009), sperm concentration (median concentration 16 × 106/ml vs. 31 × 106/ml, P = 0.009) and total sperm count (median count 46 × 106 vs. 82 × 106, P = 0.009) than men with hrHPV negative samples. No association was identified between penile hrHPV status and semen parameters. Conclusions Our findings indicate that penile HPV infection is common in both potential sperm donors and men from infertile couples. Although HPV positivity is higher in penile swabs, only HPV infection in semen samples affects sperm parameters. However, there was no association between hrHPV positivity in semen and fertility outcomes including abortion rate.